Analisis Rasio Keuangan Pada Koperasi Karyawan PDAM Tirta Musi Palembang - Irsan; Roy Saleh; Hilwa Anggraini; Masnoni; Nelly (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2019)
The purpose of this study was to determine the financial performance of the Tirta Musi PDAM Employee Cooperative as measured by liquidity ratios, solvency ratios, and profitability ratios during the 2016 to 2018 period at the Tirta Musi PDAM Employee Cooperative in Palembang. This type of qualitative descriptive research with a quantitative approach, using secondary data in the form of financial reports. The results of the study in terms of the liquidity ratio using the current ratio show that the current ratio is in a very unhealthy category, this happens because the current ratio increases every year due to the amount of receivables owned by the cooperative. Judging from the solvency ratio using two methods, namely the debt to total assets ratio and the debt to equity ratio, the cooperative employees of PDAM Tirta Musi are in good health, this happens because the debt to total assets ratio and debt to equity ratio decrease every year. The smaller the percentage value, the better the soundness of the solvency. Judging from the profitability / profitability ratio using three methods, namely net profit margin, return on assets, and return on equity, the profitability / profitability ratio fluctuates because the profitability ratio has increased or decreased, net profit margin and return on assets are in the unhealthy category, while returns on equity in the unhealthy category.